Language production in Croatian boys and girls of preschool age - Mildner, Vesna (Array, 2011)
There is ample evidence showing that, with respect to speech and language axquisition, girls and boys differ at early chronological age, i.e. at the time of the first word and subsequent periods, especially until age two or even three. The authors who claim that girls are verbally more advanced than boys stress the fact that they produce theri first word earlier and that they talk more than boys of comparable age. Others shift their attention to the differences in style: girls are said to favor nouns and boys supposedly favor vers in theri language production. Some cross-linguistics and cross-cultural studies have shown differences in that respect. The aim of this study was to test whether the gender differeces recorded at early verbal age persist until school age, especially since some psychological studies indicate that teachers tend to give overall higher grades to students with higer verbal abilities. The study was conducted on a sample of healthy 58 children (28 girls and 30 boys), aged five to seven years, native speakers of Croatian. They were all attending the same pre-school institution (the recordings were done in April/May 2010), and were expected to start elementary school several months after the copletion of the study (September of the same year). Upon obtaining all the necessary permissions from parents and authorities, each child completed two taskes : (a) telling a story form a series of cartoons, and (b) free conversation with the experimenter. We measured three parameters: (a) total amount of speech produced by the child ; (b) proportion of various categories of words ; and (c) vocabulary size. The only statistically significant differences between girls and boys (p<0.05) were found in the total number of nouns produced by girls on both tasks, but there was no difference between the two groups in the proportion of nouns to other word categories. Overall, no statistically significant gender differences were found on any task or parameter between the preschoolers invloved in this study. Our results indicate that any gender differences present at early stages of speech and language acquisition are equaled out by the time the children start elementary school. We attribute this, at least in part, to the fact that for three years they have all shared the same institutionalized setting and program.